Is Lexicography Making Progress? On Dictionary Use and Language Learners’ Needs - Abecassis, Michaël (Lexikos, 2007)
Abstract: This article sets out to explore the ways native speakers as well as foreign language learners use dictionaries and the strategies dictionary users adopt in the language acquisition process. The basis for this article is a corpus of six books (in chronological order Atkins (Ed.) 1998, Nesi 2000, Tono 2001, Humblé 2001, Sin-wai (Ed.) 2004 and Thumb 2004) that look at both the usage of bilingual, monolingual and bilingualised dictionaries and the users’ behaviour in the consultation process. Both the bilingual and monolingual dictionaries seem to be used independently, depending on whether the user wants to utilise them for comprehension, translation or production with regard to a foreign language. As pointed out in the literature on lexicography, some of these dictionaries, though they have undergone many changes over the years, still have serious limitations as learning tools, but the user’s performance is also under investigation in empirical research, with the aim of optimising dictionary effectiveness as well as developing the language learner’s skills.